Occurrence and genetic diversity of phosphate-solubilizing bacteria in soils of differing chemical characteristics in Kenya - Ndung'u-Magiroi, Keziah Wairimu; Herselman, L.; Okalebo, JR; Othieno, CO; Pypers, Pieter; Lesueur, Didier (Springer, 2012)
This study focused on the isolation, identification (sequencing of 16S rDNA gene) and determination of the phosphorus (P)-solubilizing efficiency of native populations of phosphate-solubilizing bacteria (PSB) in 13 Kenyan soils with differing chemical characteristics. Air-dried soil samples were serially diluted and plated on NBRIP media and enumerated. Their phosphate-solubilizing efficiency was assessed on Frioni s agar. Pearson correlation coefficients were determined between PSB populations and soil properties. The PSB populations varied among the sites tested and had a positive and significant correlation (p???0.05) with organic carbon (r?=?0.76), exchangeable calcium (r?=?0.93) and exchangeable magnesium (r?=?0.92). A total of 150 isolates were identified to the genus and species level. Among the isolates, Bacillus megaterium, Bacillus sp. and Arthrobacter sp. were the most abundant and well-distributed strains. However, only 5% of the total isolates were efficient in terms of phosphate-solubilizing efficiency. The results indicate that although there were many PSB strains in the soils tested, only a few (5%) were effective in terms of their phosphate-solubilizing ability. It is therefore unlikely that native PSB contribute significantly to solubilizing phosphate in the soils tested, which would ultimately benefit plant growth. Therefore, inoculation with effective strains with a high P solubilization potential is necessary.